Professor Lev Valeryevich Lebedev (on the 100th anniversary of his birth) - G. G. Khubulava; A. S. Nemkov (Вестник хирургии имени И.И. Грекова)
Professor Lev Valeryevich Lebedev worked at the Department of Faculty Surgery of the Pavlov University for 34 years, including 17 years as the head of the Department. On the occasion of the 100th anniversary of the birth of the surgeon, teacher and organizer of the angiosurgical service in St. Petersburg, we publish materials dedicated to the life of L. V. Lebedev, the scientific directions that he developed in Leningrad-St. Petersburg and in the 1st LMI – Pavlov University.